Molecular Investigation of Leber's Hereditary Optic Neuropathy Common Mutations in Suspected Patients - HR Soleimanpour; DD Farhud; SK Bidooki; L Andonian; M Togha; M Khanlari (Tehran University of Medical Sciences, 2004)
LHON is a mitochondrial neurodegenerative disorder often manifesting itself in the second or third decade of life, and hence resulting in progressive central vision loss usually in a short period of 2-8 weeks within which different degrees of blindness may occur. Etiologically, more than twenty missense mutations have been reported for LHON, amongst which the three mutations of G11778A, G3460A and T14484C, affecting NADH dehydrogenase complex activity, are recognized as primary mutations. The three primary mutations account for 90% of LHON patients, emphasizing the importance of molecular investigation of these mutations for differential diagnosis of LHON. Using PCR-RFLP, this research resulted in the detection of two LHON families carrying the G11778A mutation in homoplasmy and described the clinical and molecular features of the disease in the patients.